Assessing the Use of Marble Dust as a Filler in Asphalt Concrete for Durable Flexible Pavements - Arthur Ahabwe (Uganda Christian University, 2025)
Flexible pavements are the most commonly used road pavement used in Uganda and the surfacing layer is made of asphalt concrete which is a mix of aggregates, bitumen and mineral filler. The primary goal of this study was to investigate the use of marble dust as a mineral filler to improve the durability of asphalt concrete. The engineering properties of bitumen, aggregates and mineral filler were determined and tests such as the Marshall test and the indirect tensile strength test were carried out. For each mix, Marshall stability, flow, air voids, voids in mineral aggregate as well voids filled with asphalt were all determined. Air voids reduced from 4.7% to 3.8%, Marshall stability increased from 13.2 KN to 17.1 KN and indirect tensile strength increased from 899 kpa to 1,104 kpa. it was also observed that 5% of marble dust in the asphalt mix was the optimum mineral filler percentage or content to be used in the mix. Findings found that 5% of marble dust improved increased stability and stiffness of the asphalt mixtures hence making improving its resistance to rutting. In conclusion, this study demonstrates that 5% of marble dust can be used as a filler to reduce air voids, increase Marshall stability and improve the strength properties and stiffness of asphalt making it stronger and more resistant to permanent properties.
Undergraduate